Savings behavior and financial problems among college students: the role of financial literacy in Malaysia - Sabri, Mohamad Fazli; MacDonald, Maurice (Canadian Academy of Oriental and Occidental Culture, 2010)
This study analyzes the relationship of savings behavior and financial problems to financial literacy among college students in Malaysia. Controlling for correlates of financial literacy, multivariate analysis of a sample obtained at 11 colleges and universities demonstrated that students who had higher financial knowledge test scores were more likely to report savings behavior and also reported fewer financial problems. The influence of childhood consumer experience and financial socialization agents on savings and financial problems was more mixed, indicating that financial experience before college may create bad habits or poor attitudes toward financial management that could be mitigated through financial education during college. Implications of these findings for targeting financial education on particular kinds of students are discussed.